What do my students need? Deep analysis of student's individual cognitive ability using person diagnostic map - Moh. Irma Sukarelawan; Toni Kus Indratno; Widodo Widodo; Pratiwi Dwijananti; Fitri Nur Hikmah; Nurul Syafiqah Yap Abdullah (Momentum: Physics Education Journal, 2024)
This research aims to evaluate students' conceptual understanding in the field of physics, focusing on the concepts of heat and temperature, using the Person Diagnostic Map (PKMAPs) approach. This method allows individual assessment of students' conceptual understanding, going beyond the limitations of conventional analysis methods that focus on groups. This research used a survey involving eight students from a private university in Yogyakarta, Indonesia. Data was collected through a multiple-choice test of 20 items, processed using Ms. Excel and Winsteps 4.6.1. The research results show that PKMAPs are effective in identifying individual student understanding, including detecting "correct" response patterns resulting from guessing or cheating, as well as "incorrect" response patterns caused by incompetence or inaccuracy. This information allows educators to determine appropriate teaching methods, including remediation, re-teaching, or enrichment, according to each student's individual needs. This research concludes that using the Person Diagnostic Map in the context of physics education provides a more personal and effective approach to analyzing students' conceptual understanding. This method provides deeper insight into students' individual strengths and weaknesses, facilitating more focused and effective learning planning.